Nanocomposite Bienzymatic Sensor for Monitoring Xanthine in Wound Diagnostics. Issue 9 (10th June 2019) - RoyChoudhury, Sohini; Umasankar, Yogeswaran; Bhushan, Pulak; Hirt, Penelope A.; MacQuhae, Flor E.; Borda, Luis J.; Lev-Tov, Hadar A.; Kirsner, Robert; Bhansali, Shekhar
Abstract : This work reports a biosensor for monitoring xanthine for potential wound healing assessment. Active substrate of the biosensor has xanthine oxidase (XO) and horseradish peroxidase (HRP) physisorbed on a nanocomposite of multiwalled carbon nanotubes (MWCNT) decorated with gold nanoparticles (AuNP). The presence of HRP provided a two-fold increase in response to xanthine, and a three-fold increase in response to the nanocomposite. With a sensitivity of 155.71 nA μM −1 cm −2 the biosensor offers a detection limit of 1.3 μM, with linear response between 22 μM and 0.4 mM. Clinical sample analyses showed the feasibility of xanthine detection from biofluids in a lesion site due to diffusion of the analyte into surrounding biofluids. Higher concentrations by three-fold were observed from wound proximity, than away from injury, with an average recovery of 110%. Results show the feasibility of monitoring wound severity through longitudinal measurements of xanthine from injured vicinity.